Congenital heart defects in calves. (9th July 2021) - Millar, Michael; Foster, Aiden; Borgeat, Kieran; Adams, James; Woollatt, Sarah; Floyd, Toby; Jewell, Natalie; Swinson, Vanessa; Moore, Jonathan; Strugnell, Ben
Abstract : This focus article describes some of the cardiac anomalies detected in calves submitted to APHA Veterinary Investigation Centres and other postmortem examination providers